Utilizing POE (Predict-Observe-Explain) Learning Model to Enhance Studentsâ Learning Outcome in Science - Dewi, Rukmana; Antosa, Zariul; Astuti, Eva; Noviana, Eddy; Hermita, Neni (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine enhanching studentsâ science learning outcomes before and after applying the POE (predict-observe-explain) learning model. This type of research is a pre-experimental type one-group pretest-posttest design, which is an experiment carried out on only one group, without comparison. This research was conducted in 4 of 38 students. Based on the results of the study, it was found that the average score of learning outcomes before treatment (pretest) was 57.89 while the average score of learning outcomes after treatment (posttest) was 80.63 and the average value of gain was 0.56 which included medium interpretation, and the results of hypothesis testing using t-test with t count = 12.92 and t table = 2.0374 then concluded tcount> t table, then reject H0 means significant. This means that there is an increase in grade IV learning outcomes for students between before (pretest) and after (posttest) applying the POE (predict-observe-explain) learning model. This shows that the POE (predict-observe-explain) learning model can improve the learning outcomes of elementary school students in natural resource material.